Implementasi Inovasi Kebijakan Program Rebo Nyunda di Pemerintah Kota Bandung - Wahyu R, Ginulur; Baihaqi, Muhammad Rifqi; Nurhayadi, Nurhayadi; Tamimi, Tamimi; Candith, Juliannes (Fakultas Ilmu Administrasi Universitas Subang, 2024)
This research is motivated by the desire of researchers to know and analyze the optimization of Sundanese cultural characters through the Rebo Nyunda program that was realized by the Bandung city government. The Rebo Nyunda program is a Bandung city government program as part of the thematic days that apply in the city. This program is also one of the programs to preserve Sundanese culture because of the flow of modernization that cannot be avoided by all layers and technological advances that are faster than the progress of values and culture, and today the city is a very dynamic urbanization city. So with that the Bandung city government must be open to all residents of the region. The method in this research uses descriptive method with a qualitative approach. The results of the study were obtained through an interview process and document study. From the results of this study it was found that the program was less / not optimal.